The face of the Prophet In the mirror of Sheikh Ma'roof Nodhi - Mirawi, Dr. Mohammed Zuber Bayazi (Sulaimani Journal for Humanities, 2024)
During the storied history of Islam, psychology and literature have acquired a unique characteristic. Among the poetic and literary works in various languages, there are many valuable signs of praise of the Prophet (peace be upon him) that sometimes non-Muslim scholars and writers have expressed this feeling. The praise of the Prophet (peace be upon him) is very prominent in Kurdish, Arabic and Persian literature and has given a new spirit to the literature of these nations. Poetry and poetry among any people and tribe, regardless of their views, ideas and religions, is a mirror that reflects all their thoughts and beliefs, which has a wide impact on the expression of the feelings of listeners. In the texts of the works of the late Sheikh Ma'roof Nodhi, a prominent religious, scientific and mystical personality of Kurdistan, there are many examples of praise of the Prophet (peace be upon him). The purpose of this study is to show how and why Shaykh Ma'roof began to express his love and praise of the Prophet (peace be upon him) with a view of faith. Another objective of this research is to literarily interpret the content of the poems. In general, an attempt has been made to discuss the character of the Prophet (peace and blessings of Allaah be upon him) in the poems of Shamil al-Awamal by Shaykh Ma'roof. A closer look at all the poems of the Shaykh shows that he had a special love for the Prophet (peace be upon him) and it can be said that Shaykh Ma'roof gave a personal wealth to his poems by taking advantage of the praise of the Prophet. The methodology of this research is based on restorative interpretation and according to library sources.
Keywords: Sheikh Maroof; Praise and Love; Shamil; Psychology; Poems